Odpowiedź :
[tex] \\\\ x=\frac{1}{3} \\\\ y=9 \\\\ a) \\\\ 2x^2-xy^2-5x^2+2xy^2=\\\\ =2\cdot (\frac{1}{3})^2-\frac{1}{3} \cdot 9^2 -5 \cdot (\frac{1}{3})^2+2 \cdot \frac{1}{3} \cdot 9^2 =\\\\=\frac{2}{9}-27-\frac{5}{9} +54=-\frac{1}{3}+27=26 \frac{2}{3} \\\\\\\ [/tex]
[tex]\\\\\\\\\\\ b) \\\\ -\frac{1}{3}x^3y-\frac{2}{3}xy+\frac{1}{3}x^3y-\frac{1}{3}xy=\\\\ -=\frac{1}{3} \cdot (\frac{1}{3})^3 \cdot 9 -\frac{2}{3} \cdot \frac{1}{3} \cdot 9 +\frac{1}{3} \cdot (\frac{1}{3})^3 \cdot 9 -\frac{1}{3} \cdot \frac{1}{3} \cdot 9=\\\\ =-\frac{1}{9}-2+\frac{1}{9}-1=-3[/tex]
a) 2x² - xy² - 5x² + 2xy² = -3x² + xy² = -3 * 1/9 + 1/3 * 81 = -1/3 + 27 = 26 i 2/3
b) -½x³y - ⅔xy + ½x³y - ⅓xy = - xy = - 1/3 * 9 = - 3